Innate Immune-Modulatory Activity of Prunella vulgaris in Thyrocytes Functions as a Potential Mechanism for Treating Hashimoto’s Thyroiditis - Chen, Fei; Kawashima, Akira; Luo, Yuqian; Kiriya, Mitsuo; Suzuki, Koichi (Frontiers in Endocrinology, 2020)
Prunella vulgaris (PV), a perennial herb, has been used to treat thyroid diseases in China for over 2,000 years. In particular, its therapeutic effect has been described for Hashimoto’s thyroiditis, including reducing titers autoantibodies against thyroid peroxidase and thyroglobulin of and T helper 17 (Th17) cells. However, the underlying mechanism for how PV exerts such effects has not been investigated. We examined the effects of PV on innate immune activation, which is thought to be one of the triggers for the development of autoimmune diseases, including Hashimoto’s thyroiditis. In cultured thyrocytes, PV reduced mRNA levels of inflammatory cytokines that were originally induced as a result of innate immune activation initiated by transfection of double-stranded DNA (dsDNA) or dsRNA. PV suppressed activation of nuclear factor B (NF-B) and interferon regulatory factor 3 (IRF3), and suppressed corresponding promoter activation, which were initially activated by dsDNA or dsRNA. PV also suppressed the mRNA levels of molecules responsible for antigen processing and presentation, and PV protected thyrocytes from apoptosis induced by dsDNA and dsRNA. Additionally, PV suppressed the expression of genes involved in iodide uptake and oxidation. Taken together, these results suggest that PV exerts its protective effect on thyrocytes by suppressing both innate and adaptive immune responses and cell death. PV may also protect cells from iodide-associated oxidative injury. This report is among the first to identify the mechanisms to explain PV’s beneficial effects in Hashimoto’s thyroiditis.